Pengaruh Pengawasan Terhadap Disiplin Kerja Karyawan Pada PT. SPPR Pekanbaru - Innasyrulah, Innasyrulah; yapentra, arhipen (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
This research aims to determine the effect of supervision on employee work discipline carried out at PT. Suryakarsa Puspita Prima Pekanbaru. The sample taken in this research was 57 people. In analyzing data, this research uses descriptive and quantitative methods. This descriptive method aims to describe the relationship between actual reality and related theories. The results can be drawn to conclusions and tabulated in table form, then analyzed according to the research objectives. Meanwhile, quantitative methods are used to determine the relationship between the independent variable (X) and the dependent variable (Y) using statistical equipment using the simple linear regression method. This is proven by the simple regression equation Y = 5.551 + 0.678 From the determination test, it is known that (R2) is 0.451, which means that the supervision variable has an influence of 41.5% on employee work discipline at PT. Suryakarsa Puspita Prima Pekanbaru, the remaining 54.9% is influenced by variable factors that were not examined.